2011
DOI: 10.2208/jscejoe.67.i_310
|View full text |Cite
|
Sign up to set email alerts
|

Development of Numerical Larval Model Based on Swimming Behavior for Larval Snow Crab Reared in the Laboratory

Abstract: The planktonic larval snow crab Chionoecetes opilio come up to near the sea surface induced by underwater light after hatching, and start descending when their weight, which increases with growth, exceeds the upward force produced by their swimming behavior towards the surface. Based on these activities, we developed a model representing the swimming pattern of the planktonic larvae until they acquire settlement. The larvae were put in the experimental tank with the same water conditions, and a monochromatic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Laboratory experiments have shown that larval behaviour changes in response to abiotic and biotic factors, including light intensity and wavelength, barometric pressure, gravity, temperature, salinity and chemical cues from predators (Sulkin 1984;Forward 1988Forward , 2009). Moreover, the direction of larval swimming can be modelled in terms of drag forces, the downward gravitational force and the upward buoyant force (Konishi et al 2011); body density is an important dimension for calculating these parameters. However, larval body density has been examined for only a few decapod crustacean species (Mizumoto et al 2012;Hamasaki et al 2013;Ichikawa et al 2014), and no study has investigated the ontogeny of larval body density in relation to the moulting cycle.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 4 more Smart Citations
“…Laboratory experiments have shown that larval behaviour changes in response to abiotic and biotic factors, including light intensity and wavelength, barometric pressure, gravity, temperature, salinity and chemical cues from predators (Sulkin 1984;Forward 1988Forward , 2009). Moreover, the direction of larval swimming can be modelled in terms of drag forces, the downward gravitational force and the upward buoyant force (Konishi et al 2011); body density is an important dimension for calculating these parameters. However, larval body density has been examined for only a few decapod crustacean species (Mizumoto et al 2012;Hamasaki et al 2013;Ichikawa et al 2014), and no study has investigated the ontogeny of larval body density in relation to the moulting cycle.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A number of studies have elucidated the general biology of snow crab larvae, focused on managing stocks or on the mechanisms of fluctuations in stock abundance (e.g., Kon 1980;Incze et al 1984;Davidson & Chin 1991;Lovrich & Ouellet 1994). Their phototactic and geotactic behaviours have been studied to better understand the mechanisms of their spatiotemporal distribution (Kogane et al 2007;Konishi et al 2011). However, their body densities were measured using specimens preserved in formalin solutions (Konishi et al 2011) and might not reflect values in living animals.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 3 more Smart Citations